Comparative efficacy of electrokinetic and static leaching for selective metal recovery and nutrient release from porphyry Cu tailings - Yujie Yan; Gawen R.T. Jenkin; Andrew P. Abbott; Alexandria Tanciongco; Carlo A. Arcilla; Cris Reven L. Gibaga; Daniel J. Smith; Djoan Kate Tungpalan; Jonathan E. Chambers; John Henry C. Gervasio; James Symons; Justine Perry T. Domingo; et al. (Chemical Engineering Journal, 2026)

Assessing population exposure to airborne fungi in the UK over one year using high-throughput sequencing (HTS) metabarcoding methods - Philippa Douglas; Samuel Anees-Hill; Sameirah Macchiarulo; Fiona A. Symon; Jack Satchwell; Anna L. Hansell; Emma L. Marczylo (Environmental Research, 2025)

Wildfire smoke impacts lake ecosystems - Mary Jade Farruggia; Janice Brahney; Andrew J. Tanentzap; Jennifer A. Brentrup; Ludmila S. Brighenti; Sudeep Chandra; Alicia Cortés; Rocio L. Fernandez; Janet M. Fischer; Alexander L. Forrest; Yufang Jin; Kenneth Larrieu; et al. (Global Change Biology, 2024)
Wildfire activity is increasing globally. The resulting smoke plumes can travel hundreds to thousands of kilometers, reflecting or scattering sunlight and depositing particles within ecosystems. Several key physical, chemical, and biological processes in lakes are controlled by factors affected by smoke. The spatial and temporal scales of lake exposure to smoke are extensive and under‐recognized. We introduce the concept of the lake smoke‐day, or the number of days any given lake is exposed to smoke in any given fire season, and quantify the total lake smoke‐day exposure in North America from 2019 to 2021. Because smoke can be transported at continental to intercontinental scales, even regions that may not typically experience direct burning of landscapes by wildfire are at risk of smoke exposure. We found that 99.3% of North America was covered by smoke, affecting a total of 1,333,687 lakes ≥10 ha. An incredible 98.9% of lakes experienced at least 10 smoke‐days a year, with 89.6% of lakes receiving over 30 lake smoke‐days, and lakes in some regions experiencing up to 4 months of cumulative smoke‐days. Herein we review the mechanisms through which smoke and ash can affect lakes by altering the amount and spectral composition of incoming solar radiation and depositing carbon, nutrients, or toxic compounds that could alter chemical conditions and impact biota. We develop a conceptual framework that synthesizes known and theoretical impacts of smoke on lakes to guide future research. Finally, we identify emerging research priorities that can help us better understand how lakes will be affected by smoke as wildfire activity increases due to climate change and other anthropogenic activities.

Comparisons of aerosol generation across different musical instruments and loudness - Jianghan Tian; Henry E. Symons; Natalie A. Watson; Justice Archer; Lauren P. McCarthy; Joshua Harrison; Malcolm Kittle; William J. Browne; Brian Saccente-Kennedy; Ruth Epstein; Christopher M. Orton; James D. Calder; et al. (Journal of Aerosol Science, 2024)

Association between ambient temperature and common allergenic pollen and fungal spores: A 52-year analysis in central England, United Kingdom - Holly C.Y. Lam; Samuel Anees-Hill; Jack Satchwell; Fiona Symon; Helen Macintyre; Catherine H. Pashley; Emma L. Marczylo; Philippa Douglas; Stuart Aldridge; Anna Hansell (Science of The Total Environment, 2024)

Fire transforms effects of terrestrial subsidies on aquatic ecosystem structure and function - Christopher B. Wall; Cody J. Spiegel; Evelyn M. Diaz; Cindy H. Tran; Alexia Fabiani; Taryn Y. Broe; Elisabet Perez‐Coronel; Sara L. Jackrel; Natalie Mladenov; Celia C. Symons; Jonathan B. Shurin (Global Change Biology, 2024)
Fire can lead to transitions between forest and grassland ecosystems and trigger positive feedbacks to climate warming by releasing CO 2 into the atmosphere. Climate change is projected to increase the prevalence and severity of wildfires. However, fire effects on the fate and impact of terrestrial organic matter (i.e., terrestrial subsidies) in aquatic ecosystems are unclear. Here, we performed a gradient design experiment in freshwater pond mesocosms adding 15 different amounts of burned or unburned plant detritus and tracking the chronology of detritus effects at 10, 31, 59, and 89 days. We show terrestrial subsidies had time‐ and mass‐dependent, non‐linear impacts on ecosystem function that influenced dissolved organic carbon (DOC), ecosystem metabolism (net primary production and respiration), greenhouse gas concentrations (carbon dioxide [CO 2 ], methane [CH 4 ]), and trophic transfer. These impacts were shifted by fire treatment. Burning increased the elemental concentration of detritus (increasing %N, %P, %K), with cascading effects on ecosystem function. Mesocosms receiving burned detritus had lower [DOC] and [CO 2 ] and higher dissolved oxygen (DO) through Day 59. Fire magnified the effects of plant detritus on aquatic ecosystem metabolism by stimulating photosynthesis and respiration at intermediate detritus‐loading through Day 89. The effect of loading on DO was similar for burned and unburned treatments (Day 10); however, burned‐detritus in the highest loading treatments led to sustained hypoxia (through Day 31), and long‐term destabilization of ecosystem metabolism through Day 89. In addition, fire affected trophic transfer by increasing autochthonous nitrogen source utilization and reducing the incorporation of 15 N‐labeled detritus into plankton biomass, thereby reducing the flux of terrestrial subsidies to higher trophic levels. Our results indicate fire chemically transforms plant detritus and alters the role of aquatic ecosystems in processing and storing carbon. Wildfire may therefore induce shifts in ecosystem functions that cross the boundary between aquatic and terrestrial habitats.

Intermittent instability is widespread in plankton communities - Tanya L. Rogers; Stephan B. Munch; Shin‐ichiro S. Matsuzaki; Celia C. Symons (Ecology Letters, 2023)
Chaotic dynamics appear to be prevalent in short‐lived organisms including plankton and may limit long‐term predictability. However, few studies have explored how dynamical stability varies through time, across space and at different taxonomic resolutions. Using plankton time series data from 17 lakes and 4 marine sites, we found seasonal patterns of local instability in many species, that short‐term predictability was related to local instability, and that local instability occurred most often in the spring, associated with periods of high growth. Taxonomic aggregates were more stable and more predictable than finer groupings. Across sites, higher latitude locations had higher Lyapunov exponents and greater seasonality in local instability, but only at coarser taxonomic resolution. Overall, these results suggest that prediction accuracy, sensitivity to change and management efficacy may be greater at certain times of year and that prediction will be more feasible for taxonomic aggregates.

Predicting Seabird Foraging Habitat for Conservation Planning in Atlantic Canada: Integrating Telemetry and Survey Data Across Thousands of Colonies - Robert A. Ronconi; David J. Lieske; Laura A. McFarlane Tranquilla; Sue Abbott; Karel A. Allard; Brad Allen; Amie L. Black; François Bolduc; Gail K. Davoren; Antony W. Diamond; David A. Fifield; Stefan Garthe; et al. (Frontiers in Marine Science, 2022)
Conservation of mobile organisms is difficult in the absence of detailed information about movement and habitat use. While the miniaturization of tracking devices has eased the collection of such information, it remains logistically and financially difficult to track a wide range of species across a large geographic scale. Predictive distribution models can be used to fill this gap by integrating both telemetry and census data to construct distribution maps and inform conservation goals and planning. We used tracking data from 520 individuals of 14 seabird species in Atlantic Canada to first compare foraging range and distance to shorelines among species across colonies, and then developed tree-based machine-learning models to predict foraging distributions for more than 5000 breeding sites distributed along more than 5000 km of shoreline. Despite large variability in foraging ranges among species, tracking data revealed clusters of species using similar foraging habitats (e.g., nearshore vs. offshore foragers), and within species, foraging range was highly colony-specific. Even with this variability, distance from the nesting colony was an important predictor of distribution for nearly all species, while distance from coastlines and bathymetry (slope and ruggedness) were additional important predictors for some species. Overall, we demonstrated the utility of tree-based machine-learning approach when modeling tracking data to predict distributions at un-sampled colonies. Although tracking and colony data have some shortcomings (e.g., fewer data for some species), where results need to be interpreted with care in some cases, applying methods for modeling breeding season distributions of seabirds allows for broader-scale conservation assessment. The modeled distributions can be used in decisions about planning for offshore recreation and commercial activities and to inform conservation planning at regional scales.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

When are bacteria really gazelles? Comparing patchy ecologies with dimensionless numbers - Samuel S. Urmy; Alli N. Cramer; Tanya L. Rogers; Jenna Sullivan‐Stack; Marian Schmidt; Simon D. Stewart; Celia C. Symons (Ecology Letters, 2022)
From micro to planetary scales, spatial heterogeneity—patchiness—is ubiquitous in ecosystems, defining the environments in which organisms move and interact. However, most large‐scale models still use spatially averaged ‘mean fields’ to represent natural populations, while fine‐scale spatially explicit models are mostly restricted to particular organisms or systems. In a conceptual paper, Grünbaum (2012, Interface Focus 2: 150–155) introduced a heuristic, based on three dimensionless ratios quantifying movement, reproduction and resource consumption, to characterise patchy ecological interactions and identify when mean‐field assumptions are justifiable. We calculated these dimensionless numbers for 33 interactions between consumers and their resource patches in terrestrial, aquatic and aerial environments. Consumers ranged in size from bacteria to whales, and patches lasted from minutes to millennia, with separation scales from mm to hundreds of km. No interactions could be accurately represented by naive mean‐field models, though 19 (58%) could be partially simplified by averaging out movement, reproductive or consumption dynamics. Clustering interactions by their non‐dimensional ratios revealed several unexpected dynamic similarities. For example, bacterial Pseudoalteromonas exploit nutrient plumes similarly to Mongolian gazelles grazing on ephemeral steppe vegetation. We argue that dimensional analysis is valuable for characterising ecological patchiness and can link widely different systems into a single quantitative framework.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Trophic control changes with season and nutrient loading in lakes - Tanya L. Rogers; Stephan B. Munch; Simon D. Stewart; Eric P. Palkovacs; Alfredo Giron‐Nava; Shin‐ichiro S. Matsuzaki; Celia C. Symons (Ecology Letters, 2020)
Experiments have revealed much about top‐down and bottom‐up control in ecosystems, but manipulative experiments are limited in spatial and temporal scale. To obtain a more nuanced understanding of trophic control over large scales, we explored long‐term time‐series data from 13 globally distributed lakes and used empirical dynamic modelling to quantify interaction strengths between zooplankton and phytoplankton over time within and across lakes. Across all lakes, top‐down effects were associated with nutrients, switching from negative in mesotrophic lakes to positive in oligotrophic lakes. This result suggests that zooplankton nutrient recycling exceeds grazing pressure in nutrient‐limited systems. Within individual lakes, results were consistent with a ‘seasonal reset’ hypothesis in which top‐down and bottom‐up interactions varied seasonally and were both strongest at the beginning of the growing season. Thus, trophic control is not static, but varies with abiotic conditions – dynamics that only become evident when observing changes over large spatial and temporal scales.

Training fish for restocking: refuge and predator training in the hatchery has limited benefits for a marine fish - David L. Rae; Benjamin Mos; Anna Scott; Symon A. Dworjanyn (Journal of Fish Biology, 2020)
Large numbers of hatchery‐reared fish are released in stocking programmes; however, success is limited by high mortality. Predation is seen as the main cause of deaths but might be reduced by training fish before release to avoid predators and/or use refuge. In this study on a potential restocking species, yellowfin bream Acanthopagrus australis , the effects of predator training and refuge on the behaviour of fish in the hatchery were tested. In the first experiment, juvenile bream were exposed to predatory mangrove jack ( Lutjanus argentimaculatus ) fed exclusively on bream flesh while housed in tanks with and without refuge. Predator training altered fish behaviour when fish were re‐exposed to predators, but the effects were subtle and varied between groups of fish. In contrast, refuge created strong and consistent changes in behaviour, significantly slowing down the amount of time that fish took to consume food. A second experiment focused on the effects of refuge. Bream were trained to use artificial seagrass or house bricks as refuge and then exposed to mangrove jacks in a laboratory predation experiment. When refuge was available, fish significantly slowed down their feeding rate. There was a small, transient increase in survival for fish given seagrass refuges, but this was irrespective of whether the bream were trained to use refuge. The results of this study indicate that the use of refuge may be innate and the benefits of refuge may be available to naive hatchery‐reared fish or fish trained to use refuge shortly before release. This suggests that there is potential to improve post‐release survival of fingerlings without time‐consuming and expensive hatchery training.

Integrating team science into interdisciplinary graduate education: an exploration of the SESYNC Graduate Pursuit - Kenneth E. Wallen; Karen Filbee-Dexter; Jeremy B. Pittman; Stephen M. Posner; Steven M. Alexander; Chelsie L. Romulo; Drew E. Bennett; Elizabeth C. Clark; Stella J.M. Cousins; Bradford A. Dubik; Margaret Garcia; Heather A. Haig; et al. (Journal of Environmental Studies and Sciences, 2019)

Biogenic acidification drives density-dependent growth of a calcifying invertebrate in culture - Benjamin Mos; Maria Byrne; Kenneth L. Cowden; Symon A. Dworjanyn (Marine Biology, 2015)

Seasonal variation in the effects of ocean warming and acidification on a native bryozoan, Celleporaria nodulosa - Halley M. S. Durrant; Graeme F. Clark; Symon A. Dworjanyn; Maria Byrne; Emma L. Johnston (Marine Biology, 2013)

Infection rate and colonization with antibiotic-resistant organisms in skilled nursing facility residents with indwelling devices - L. Wang; B. Lansing; K. Symons; E. L. Flannery; J. Fisch; K. Cherian; S. E. McNamara; L. Mody (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Dissolved histamine: a potential habitat marker promoting settlement and metamorphosis in sea urchin larvae - Rebecca L. Swanson; Maria Byrne; Thomas A. A. Prowse; Benjamin Mos; Symon A. Dworjanyn; Peter D. Steinberg (Marine Biology, 2012)

The Reocín zinc–lead deposit, Spain: paleomagnetic dating of a late Tertiary ore body - David T. A. Symons; Michael T. Lewchuk; Kazuo Kawasaki; Francisco Velasco; David L. Leach (Mineralium Deposita, 2009)

Torque loss induced by repetitive maximal eccentric contractions is marginally influenced by work-to-rest ratio - Chris J. McNeil; Brian L. Allman; T. Brock Symons; Anthony A. Vandervoort; Charles L. Rice (European Journal of Applied Physiology, 2004)

Reply to Discussion on "Mississippi Valley-type lead–zinc deposits through geological time: implications from recent age-dating research" by S.E. Kesler and C.W. Carrigan (2001) Mineralium Deposita 36:711–740 - David L. Leach; Dwight Bradley; Michael Lewchuk; David T. Symons; Wayne Premo; Joyce Brannon; Ghislain de Marsily (Mineralium Deposita, 2002)

Mississippi Valley-type lead–zinc deposits through geological time: implications from recent age-dating research - David L. Leach; Dwight Bradley; Michael T. Lewchuk; David T. Symons; Ghislain de Marsily; Joyce Brannon (Mineralium Deposita, 2001)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)